Gambaran Karekteristik Fraktur Radius Dital di RSUD Abdul Wahab Sjahranie Samarinda Tahun 2017-2019: Overview of Distal Radius Fracture Characteristics at Abdul Wahab Sjahranie Hospital, Samarinda in 2017-2019 - Muhammad Abduh Bachrl Ihza; Gregorius Tekwan; Abdul Mu’ti (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2022)
Distal Radius Fractures are the most common fractures in the world. 17.5% of fractures are categorized as distal radius fractures. Distal radius fractures can occur in both young age and old age. Distal radius fractures mostly occur in young adult age group due to high-energy trauma, and in senior age group due to low-energy trauma and osteoporosis. This research aims to capture the overview of distal radius fracture characteristics at RSUD (Rumah Sakit Umum Daerah – Regional Public Hospital) Abdul Wahab Sjahranie Samarinda. The data in this research are secondary data, gathered from medical records of patients. This research was performed in February 2021. This research is a Descriptive Retrospective study. 146 patients diagnosed with distal radius fractures from January 2017 – December 2019 were selected as samples, using Total Sampling method. The result showed that most cases of distal radius fractures occurred in 10-19 years age group (29 patients, 19.9%), male (87 patients, 59.6%), students (47 patients, 34.2%). Furthermore, the most common type of fractures found was closed fracture type (137 patients, 93.8%), the most common clinical fracture found was unidentified fracture (65 patients, 44.5%), and the most common cause of fractures was from trauma (90 patients, 61.6%).